Research on the full life cycle safety of levee based on BIM+mechanism algorithm - Hou, Yi; Yu, Jindi; Liu, Wei; Li, Yueting; Zhang, Feng (Archives of Civil Engineering, 2026)
Levee is the oldest and most widely used water conservancy project in human society, and its safety is directly related to the safety of people's lives and property. According to current regulations, calculations about seepage stability and sliding stability are required during the design and operation management of levees,which including section modeling, soil index organization and boundary condition setting. Due to the characteristic of long distance and multiple sections, these calculations are time-consuming, labor-intensive, and prone to manual errors. This article proposes an innovative research method for the full life cycle safety of levees based on BIM+Mechanisma algorithm. Take West danger Levee project for example, firstly study the three-dimensional geological modeling of levees based on databases, providing the physical and mechanical properties data of geological strata for subsequent calculations; then improve the efficiency of structural modeling and modification by BIM parametric design; finally, construct BIM+GIS data base to integrate the structural and geological information. Then, this article develops finite element seepage calculation program and limit equilibrium method calculation program, further more providing data and functional interfaces to support online calling of external programs. The above research is used for levee design, extracting calculation models from design sections and calling calculation modules for batch solving, hereby improving the situation where levee design and calculations are separated from each other and enhancing design optimization efficiency. On the other hand, applied to digital twin, the safety data base and Mechanism Algorithms of levee are used for safety evaluation after construction.